Design and development of web-based Career Management System in UiTM (Career Unit) / Aryanti Md Dris @ Shaari - Md Dris @ Shaari, Aryanti (2006)
Currently, UiTM has its own website for Career unit (Career & Employer Relation Department). The current website has introduced the career unit to others that are interested rather than helping the students to find job especially for job seekers. The website was lack of its functionality and could be expanded for purpose to match person with jobs available. The students also found that jobs in many alternative ways such as advertisement in newspapers. The traditional way took a longer time and rather slow to know the feedback of application. The employees also needed more effective way to find their candidates for job interviews. Advertising in newspaper was rather slow. Therefore, a web-based of Career Management System (CMS) was designed to solve the problems. Basically the proposed system was categorized in two levels which are administrator and jobseeker. In developing the system in to be interactive, the software that used were Macromedia Dream weaver as design interface, Apache as web server. Personal home page (PHP) for server side scripting language and MySQL for database. The research implemented by using Web Development Life Cycle. As a result, this project has generated solution job seekers especially Uitm students to submit their CV and seek jobs in the easiest way. Thus, the qualification and application could be matched and they got faster feedback. As the conclusion, this project improves mobilization of the human resources and ensures the manpower utilization is optimized through the systematic matching of job seekers to job vacancies.